Dilution effect on thermal performances and NOx emission characteristics of an ammonia-oxygen micro-thermophotovoltaic system. (1st September 2022) - Sun, Yuze; Zhao, Dan; Cai, Tao
Highlights: Thermal performances, emission characteristics and flammability behaviors of a diluted ammonia/oxygen micro-system are numerically investigated. The dilution could reduce the wall temperature to protect the combustor. Increasing the N2 dilution rate β N 2 leads to a decreased outer wall temperature non-uniformity and NO emissions. The flammability limit is sensitive to the dilute gas type. Abstract: Ammonia (NH3 ) is considered to be an attractive carbon-free fuel. However, the low flame speeds of ammonia/air hinder its applications. Using oxy-fuel combustion technology is an efficient method to address these issues. Nevertheless, dilution gases are still needed in oxy-combustion flames to protect the combustor and to reduce emissions. In the present work, the effects of 1) the N2 dilution rate β N 2 and 2) the dilute gas types (nitrogen, argon, or carbon dioxide) on the thermal performances, NO x emissions, and the flammability behaviors of an ammonia/oxygen micro-combustor are evaluated. Numerical results indicate that the N2 dilution rate plays a critical role in determining the thermal performances and NO emissions of the micro-combustor. It is found that increasing β N 2 is shown to be accompanied with a lower mean outer wall temperature and a higher outer wall temperature uniformity. However, a high dilution rate would lead to a sharp increase in the mean non-uniformity of the outer wall temperature R ¯ Tw and result in the flame blow-off at high flow rate conditions. The dilution rate corresponding to the maximum radiation efficiency decreases with the increase of the inlet velocity. Furthermore, increasing β N 2 contributes to the reduction of NO emissions. Finally, the effects of three types of diluting gases are evaluated by comparing the results of using 1) nitrogen, 2) argon, and 3) carbon dioxide. The present work provides a preliminary design of the diluted ammonia-oxygen micro-thermophotovoltaic system.